BARIATRIC SURGERIES AND CORRECTION OF METABOLIC DISORDERS IN PATIENTS WITH MORBID OBESITY - V. O. Khanov; D. M. Ziganshin; A. V. Shkundin; A. F. Mazitov; E. Yu. Dmitrieva (Acta Biomedica Scientifica, 2012)
The article presents the results of bariatric surgeries carried out in the clinic in patients with morbid obesity. We traced both the nearest and remote results after treatment, the loss of body weight in dynamics, relief of the manifestations of "metabolic syndrome" as well as we estimated the quality of life of patients in pre-and postoperative period.